2020
DOI: 10.1101/2020.02.24.963090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Prediction with Genotype by Environment Interaction Analysis for Kernel Zinc Concentration in Tropical Maize Germplasm

Abstract: 52Zinc (Zn) deficiency is a major risk factor for human health, affecting about 30% of the 53 world's population. To study the potential of genomic selection (GS) for maize with increased 54 Zn concentration, an association panel and two doubled haploid (DH) populations were 55 evaluated in three environments. Three genomic prediction models, M (M1: Environment + 56 Line, M2: Environment + Line + Genomic, and M3: Environment + Line + Genomic + Genomic 57 x Environment) incorporating main effects (lines and gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Given that we observed significant G×E interaction for boron, copper, iron, magnesium, and rubidium, accounting for G×E in WGP models could result in slightly improved predictive abilities for these five elements. In support of this supposition, a multi-environment model incorporating G×E resulted in higher average prediction abilities for the concentration of zinc in kernels from a tropical maize inbred panel and a double haploid population compared to those from single-environment models (Mageto et al . 2020).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Given that we observed significant G×E interaction for boron, copper, iron, magnesium, and rubidium, accounting for G×E in WGP models could result in slightly improved predictive abilities for these five elements. In support of this supposition, a multi-environment model incorporating G×E resulted in higher average prediction abilities for the concentration of zinc in kernels from a tropical maize inbred panel and a double haploid population compared to those from single-environment models (Mageto et al . 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Whole- genome prediction (WGP) models have been found to be moderately predictive of elemental concentrations in mature grain of tropical maize populations (zinc) (Guo et al . 2020; Mageto et al . 2020) and the Ames panel (boron, calcium, copper, iron, potassium, magnesium, manganese, molybdenum, nickel, phosphorus, and zinc) (Wu et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hassen et al [105] reported the first study that explored the feasibility of breeding rice, adapted to alternate wetting and drying, using genomic prediction methods that accounted for genotype by environment interactions. Mageto et al [106] evaluated genomic prediction with G × E analysis for the level of Zn in the kernel of tropical maize germplasm and demonstrated the capability of genomic prediction to boost the breeding of plants for enhanced Zn levels in the kernel of the selected superior genotypes. Multi-environment analysis can influence G × E by applying genetic and remaining covariance roles, markers and environmental covariates, or marker with G × E [91,97,107].…”
Section: Genomic Prediction For Interaction Between Genotype and Environmentmentioning
confidence: 99%